The squeezing spectrum of a quantum emitter coupled to an optical nanostructure. (19th January 2016) - Martín-Cano, Diego; Haakh, Harald R; Agio, Mario
Abstract: We analyze the spectral properties of the reduced quantum fluctuations arising from a single two-level emitter coupled to an optical nanostructure. A closed expression for the squeezing spectrum in this hybrid system is presented that includes the effect of additional phase decoherence. We consider a metallic nanoantenna to illustrate how the hybrid system can increase the bandwidth and overcome the limits to the generation of such spectral squeezing in terms of driving field intensity and the effect of pure dephasing.